The effect of pollution production in gas burner combustion system using Curve Vane Radial Air Swirler - Mohd. Fadzli Zahari (Universiti Malaysia Perlis, 2008)
Swirling flow is a main flow produced by air swirled in gas turbine engine. Such flow is the combination of swirling and vortex breakdown. Swirling flow is widely used to stabilize the flame in combustion chamber. Its aerodynamics characteristics obtained through the merging of the swirl movement and free vortex phenomenon that collide in jet and turbulent flow. The main objectives of this project are; to investigate the swirling effect in gas burner system, to design the swirler with various angles for gas burner system that incorporates the chosen parameter, to fabricate the prototype also to evaluate the performance of the prototype.